Analisis Strategi Bersaing Bisnis Mobile Broadband - , Darwin Raja Unggul ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The evolution of technology has caused a broad of cycle in the mobile industry, where there is a big quantum when a communication transformation from voice to data and the trend data communication by mobile makes the mobile broadband become an attractive business. The potential of the business is still huge according to the growth of Smartphone product and at the same time the price is getting cheaper. Other impacts that affect the business growth are customer behavior change also the outbreak of social media mostly done in mobile. The internet has shown the contribution to the development of the economy of Indonesia. Beside demografi, the other reasons, the business growth is growing and the company sees the business is the the new generation revenue base. Based on the number of players, the structure of competition in the industry is heading to the hyper competition. The company's competitive strategy was aim to products and services that can provide more values to the customers. Products and type of service packages offered in the industry are relatively same, so the price is a very sensitive to the customerâs mind. The company's positionhas influenced by the company's ability to both capitalize the strengths and minimize weaknesses. The company has carried out the competitive strategy by presenting a variant of products and services package with the latest technological capabilities. Strategic moves of the company in marketing penetration is still relevant and powerful to increase the number of subscribers, revenue and obtain a positive perception from the customers.